Separable dorsal raphe dopamine projections mimic the facets of a loneliness-like state - Christopher R Lee; Gillian A Matthews; Mackenzie E Lemieux; Elizabeth M Wasserlein; Matilde Borio; Raymundo L Miranda; Laurel R Keyes; Gates P Schneider; Caroline Jia; Andrea Tran; Faith Aloboudi; May G Chan; et al. (eLife)
Affiliative social connections facilitate well-being and survival in numerous species. Engaging in social interactions requires positive or negative motivational drive, elicited through coordinated activity across neural circuits. However, the identity, interconnectivity, and functional encoding of social information within these circuits remains poorly understood. Here, we focus on downstream projections of dorsal raphe nucleus (DRN) dopamine neurons (DRNDAT) in mice, which we previously implicated in social motivation alongside an aversive affective state. We show that three prominent DRNDAT projections – to the bed nucleus of the stria terminalis (BNST), central amygdala (CeA), and posterior basolateral amygdala (BLP) – play separable roles in behavior, despite substantial collateralization. Photoactivation of the DRNDAT-CeA projection promoted social behavior and photostimulation of the DRNDAT-BNST projection promoted exploratory behavior, while the DRNDAT-BLP projection supported place avoidance, suggesting a negative affective state. Downstream regions showed diverse receptor expression, poising DRNDAT neurons to act through dopamine, neuropeptide, and glutamate transmission. Furthermore, we show ex vivo that the effect of DRNDAT photostimulation on downstream neuron excitability depended on region and baseline cell properties, resulting in excitatory responses in BNST cells and diverse responses in CeA and BLP. Finally, in vivo microendoscopic cellular-resolution recordings in the CeA with DRNDAT photostimulation revealed a correlation between social behavior and neurons excited by social stimuli, suggesting that increased dopamine tone may recruit different CeA neurons to social ensembles. Collectively, these circuit features may facilitate a coordinated, but flexible, response in the presence of social stimuli that can be flexibly guided based on the internal social homeostatic need state of the individual.